Moving contexts onto new roads: Clues from other disciplines - Friederike Welter; Ted Baker (Institut für Mittelstandsforschung (IfM) Bonn, 2020)
This paper responds to Welter's (2011) call to pay more attention to the diversity of entrepreneurship in theorizing contexts by examining how places come to be understood as entrepreneurial. We draw briefly and selectively on ideas from a quirky set of disciplines, looking at how topics such as narratives and language, memories of the past, built environments and constellations of power among groups of people interact to shape the emergence and decline of "everyday entrepreneurship places". Our discussion illustrates some useful cues our research might draw on to challenge and improve theoretical understanding of place in entrepreneurship. – – Der Beitrag reagiert auf die Forderung von Welter (2011), der Vielfalt des Unternehmertums in theoretischen Zusammenhängen mehr Aufmerksamkeit zu schenken, indem er den Zusammenhang zwischen Orten und Unternehmertum beschreibt. Die Autoren untersuchen dabei mit Hilfe verschiedener Disziplinen wie Erzählungen und Sprache, Erinnerungen an die Vergangenheit sowie das Umfeld und Machtkonstellationen zwischen Personengruppen das Entstehen und den Niedergang von Orten des Unternehmertums beeinflussen.
Keywords: 330; contextual entrepreneurship; context; entrepreneurial place; theorizing contexts; entrepreneurship